2015
DOI: 10.1155/2015/147973
|View full text |Cite
|
Sign up to set email alerts
|

Serum Calprotectin: A Potential Biomarker for Neonatal Sepsis

Abstract: Introduction. The correct diagnosis of neonatal sepsis is a relevant problem because sepsis is one of the most important causes of neonatal morbidity, mortality, and prolonged hospital stay. Calprotectin is an antimicrobial, calcium and zinc binding heterocomplex protein that could be used as a nonspecific marker for activation of granulocytes and mononuclear phagocytes. Calprotectin has been proposed for the diagnosis of inflammatory conditions. Our aim is to study serum calprotectin as a biomarker for neonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 21 publications
3
46
1
1
Order By: Relevance
“…It has been reported that calprotectin may be considered a promising early, sensitive and specific marker of sepsis. 23 In addition, Decembrino et al 23 demonstrated that serum calprotectin concentrations are significantly higher in patients with and without neuropathy than healthy controls, suggesting that calprotectin may be a novel biomarker of neuroinflammation in diabetic peripheral neuropathy. 19 It has also been shown that serum calprotectin concentrations are increased in patients with papillary thyroid carcinoma, and the marker is positively correlated with total oxidant status and lipid hydroperoxide.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that calprotectin may be considered a promising early, sensitive and specific marker of sepsis. 23 In addition, Decembrino et al 23 demonstrated that serum calprotectin concentrations are significantly higher in patients with and without neuropathy than healthy controls, suggesting that calprotectin may be a novel biomarker of neuroinflammation in diabetic peripheral neuropathy. 19 It has also been shown that serum calprotectin concentrations are increased in patients with papillary thyroid carcinoma, and the marker is positively correlated with total oxidant status and lipid hydroperoxide.…”
Section: Discussionmentioning
confidence: 99%
“…S100A8/S100A9 proteins have pro-inflammatory properties which are characterized by the induction of pro-inflammatory cytokines and adhesion molecules in endothelial cells 34,35 . Previous findings have shown that the plasma level of S100A8/S100A9 in neonates with sepsis was found to be highly elevated 8 . The elevated level of S100A8/S100A9 amplifies inflammation and enhances the inflammatory response in infection, making it a potential therapeutic target in anti-inflammatory strategies.…”
Section: Discussionmentioning
confidence: 87%
“…Up to the present day, little is known about the course of serum calprotectin (SC) levels over time and its relationship with development of sepsis, although it was suggested by several studies as a potential marker for diagnosis in neonatal sepsis [28][29][30]. Only one study up till now studied the value of SC in identifying sepsis in adult in post-operative patients.…”
Section: Discussionmentioning
confidence: 99%